Wpływ reformy emerytalnej na kształtowanie się wielkości długu publicznego oraz deficytu sektora finansów publicznych w Polsce - Baran, Bernadeta (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
In 1999 Poland introduced the pension reform involving the establishment of capital system (with Open Pension Funds) beside the current scheme with the Social Insurance Fund - SIF. The costs of reform, which is aimed at e.g. long-term stabilization of the general government, encumber in the medium term the State Budget. Subsidy from the State Budget to SIF increases the State Budget debt servicing expenditure and the State Treasury debt. This decision has had a significant impact on the general government deficit. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1148, s. 431-441